Vapor-liquid equilibria in the systems methyl oleate + methanol & methyl oleate + water - Yong Ming, Lee (2010)
Biodiesel is now considered the next generation of replacement for petroleum and they can be easily produced from esterification of fatty acid with alcohol and this process usually requires distillation to purify the biodiesel product.For column designs and process simulation, thermodynamic properties such as vapor-liquid equilibrium data of the related components are valuable.In this present study,vapor-liquid equilibrium data for the binary systems of methyl oleate + methanol and methyl oleate + water will be measured at isobaric condition(80kPa and atmospheric pressure).The mixtures were introduced into the equilibrium cell,heated to the desired temperature and at the same time maintaining the pressure.When the system had reached equilibrium,the samples were taken and underwent evaporation using rotary evaporator to remove the more volatile component.The results taken were then correlated with UNIQUAC and NRTL-RK thermodynamic activity coefficient models and it was found out that UNIQUAC is better fitted for methyl oleate + methanol system with absolute average relative deviation(AARD) of 0.0126-0.0409 compared to the NRTL-RK with AARD of 0.396-0.4176 while NRTL-RK is better fitted for methyl oleate + water system with AARD of 0.0004039-0.0463 compared to the UNIQUAC with AARD of 0.1703-0.1948.It was also found out that the pressure will affect separation speed.With the optimum separating condition of low pressure at high temperature,it can help the industry to design a more cost effective separation column.